Volume adaptation controls stem cell mechanotransduction - Major, Luke G.; Holle, Andrew W.; Young, Jennifer; Hepburn, Matt S.; Jeong, Kwanghee; Chin, Ian L.; Sanderson, Rowan W.; Jeong, Ji Hoon; Aman, Zachary M.; Kennedy, Brendan F.; Hwang, Yongsung; Han, Dong-Wook; et al. (ACS applied materials & interfaces, 2019)
Recent studies have found discordant mechanosensitive outcomes when comparing 2D and 3D, highlighting the need for tools to study mechanotransduction in 3D across a wide spectrum of stiﬀness. A gelatin methacryloyl (GelMA) hydrogel with a continuous stiﬀness gradient ranging from 5 to 38 kPa was developed to recapitulate physiological stiﬀness conditions. Adipose-derived stem cells (ASCs) were encapsulated in this hydrogel, and their morphological characteristics and expression of both mechanosensitive proteins (Lamin A, YAP, and MRTFa) and diﬀerentiation markers (PPARγ and RUNX2) were analyzed. Low-stiﬀness regions (∼8 kPa) permitted increased cellular and nuclear volume and enhanced mechanosensitive protein localization in the nucleus. This trend was reversed in high stiﬀness regions (∼30 kPa), where decreased cellular and nuclear volumes and reduced mechanosensitive protein nuclear localization were observed. Interestingly, cells in soft regions exhibited enhanced osteogenic RUNX2 expression, while those in stiﬀ regions upregulated the adipogenic regulator PPARγ, suggesting that volume, not substrate stiﬀness, is suﬃcient to drive 3D stem cell diﬀerentiation. Inhibition of myosin II (Blebbistatin) and ROCK (Y-27632), both key drivers of actomyosin contractility, resulted in reduced cell volume, especially in low-stiﬀness regions, causing a decorrelation between volume expansion and mechanosensitive protein localization. Constitutively active and inactive forms of the canonical downstream mechanotransduction eﬀector TAZ were stably transfected into ASCs. Activated TAZ resulted in higher cellular volume despite increasing stiﬀness and a consistent, stiﬀness-independent translocation of YAP and MRTFa into the nucleus. Thus, volume adaptation as a function of 3D matrix stiﬀness can control stem cell mechanotransduction and diﬀerentiation.
Gesehen am 16.04.2020